Overpressure Evolution Simulation and Fracture Hydrocarbon Expulsion Prediction of Source Rocks in Bodong Sag, Bohai Bay Basin, China - Haifeng Yang; Lei Chen; Yanfei Gao; Tao Jiang; Changyu Fan (Geofluids)
The prediction of hydrocarbon expulsion by overpressure rupture (HEOR) is still a difficult problem in the study of primary oil and gas migration. Through thin section observation, pressure analysis, formation breakdown test, and basin numerical simulation, the overpressure fracturing of Cenozoic source rocks in Bodong Depression is studied, and its oil–gas geological significance is discussed. The research result shows that (1) overpressure is generally developed in Cenozoic source rocks in Bodong Depression, the source rocks are fractured into network fractures under the action of overpressure induced by hydrocarbon generation and undercompaction, the overpressure fractures are filled with asphalt, the rupture pressure of the source rock is controlled by the vertical principal stress, and the deep rupture pressure gradient is larger than that of the shallow layer, which makes the deep fracture more difficult; (2) the numerical simulation shows that there are two stages of rapid pressurization and one stage of slow pressurization in Bodong Sag, namely, the second thermal subsidence, the overpressure distribution in Bodong Depression has the characteristics of “strong in south and weak in north, early in south and late in north”; (3) the pressure of source rocks in the Southern Bodong Sag reached the formation rupture pressure in the rapid pressurization period since the neotectonic movement, and the hydrocarbon was quickly and efficiently expulsed. The starting times of the HEOR in Sha3 Member is 3.5 Ma~present, that in Sha1–Sha2 Member is 4~2 Ma, and that in Dong3 Member is 5.1 Ma~present. The convergent flow plus HEOR is most conducive to hydrocarbon migration and accumulation. At present, the discovered A12 and A20 oil fields developed in the path of HEOR plus convergence flow, and this study also guides the discovery of A22 oil field developed in the path of convergence flow plus HEOR.